Personal Bankruptcy and Credit Market Competition - DICK, ASTRID A.; LEHNERT, ANDREAS (Journal of Finance, 2010)
ABSTRACT We document a link between U.S. credit supply and rising personal bankruptcy rates. We exploit the exogenous variation in market contestability brought on by banking deregulation—the relaxation of entry restrictions in the 1980s and 1990s—at the state level. We find deregulation explains at least 10% of the rise in bankruptcy rates. We also find that deregulation leads to increased lending, lower loss rates on loans, and higher lending productivity. Our findings indicate that increased competition prompted banks to adopt sophisticated credit rating technology, allowing for new credit extension to existing and previously excluded households.